May neutrophil lymphocyte ratio and platelet lymphocyte ratio be used as inflammatory markers in patients with epicondylitis? Inflammatory markers in patients with epicondylitis (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine whether there is any correlation between neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and acute phase reactants such as C-reaktive protein (CRP), erythrocyte sedimentation rate (ESR) in patients with epicondylitis.Material and Methods: Our study included 274 patients. 154 patients with epicondylitis constituted the epicondylitis group and 120 healthy individuals constituted the control group. Demographic data such as age, gender, and laboratory values such as NLR and PLR were analyzed retrospectively. Both groups were compared in terms of dermographic data, leukocyte, neutrophil, lymphocyte, platelet count, CRP, ESR, NLR and PLR.Results: There was no significant differences between patient and control groups in term of demographic data such as height and weight, and laboratory values such as nuetrophil, lymphocyte, platelet, ESR and CRP (p>0,05 for all). Besides, no significant difference was found between the two groups in terms of NLR and PLR values (p>0,05 for both). There was a significant positive correlations between NLR or PLR and ESR or CRP values in the patient group (p0,001 for all).Conclusions: In our study, no significant difference was found between NLR, PLR and other blood paramaters in patients with epicondylitis compared to those of controls. As a result, we determined that it is not meaningful to use these rates to show the presence of inflammation in epicondylitis pathogenesis, and there is no correlation between the severity of epicondylitis and these rates. There is a need for further studies with more patient numbers and clinical evaluation parameters.